القوة الناعمة في السياسة الخارجية للصين (2019-2021) - الشاوش, سعود محمد (Journal of Amran University, 2022)
China's foreign policy has been cautious, driving and non-interference in other countries, and through that policy aim to achieve China's economic interests, and maintain non-political relations with other countries, especially with the United States, and for achieving those interests China has begun to pursue a policy More open to the world, using the soft force, 2019-2021 was a real test of the Chinese soft force, in this period a pandemic (Kovid -19) has emerged her first in China, and there was so much of the big repercussions On China, but on all countries of the world. Has highlighted the obstacles to the implementation of the Chinese Soft Force, and the study concluded that China has succeeded in using its soft strength in its foreign policy, during the study period, the study recommended more Of the study on soft power and how they are accounted for and reducing.